Pelatihan penggunaan Bahasa Komunikatif: Membekali Siswa Kuliner dengan Keterampilan Kewirausahaan yang Kompetitif - Aida Azizah; Evi Chamalah; Cahyo Hasanudin; Heru Muh Yasin (IKIP PGRI Bojonegoro, 2025)
ABSTRACT Training on the use of communicative language in creative project product packaging is a strategic effort to equip culinary students with competitive entrepreneurial skills. Product packaging not only functions as a protector, but also as an effective communication medium to attract consumer attention and build brand image. Through this training, students are invited to understand the importance of clear, persuasive, and informative language in product packaging. The training methods used include direct practice with the aim of providing students with a deep understanding of the importance of effective communication in packaging creative project products produced by culinary students. This can also improve students' ability to design attractive and communicative packaging. The results of the training showed a significant increase in the skills of using communicative language in product packaging. Keywords: Communicative Language; Product Packaging; Culinary Students ABSTRAK Pelatihan penggunaan bahasa komunikatif dalam kemasan produk projek kreatif merupakan upaya strategis untuk membekali siswa kuliner dengan keterampilan kewirausahaan yang kompetitif. Kemasan produk tidak hanya berfungsi sebagai pelindung, tetapi juga sebagai media komunikasi yang efektif untuk menarik perhatian konsumen dan membangun citra merek. Melalui pelatihan ini, siswa diajak untuk memahami pentingnya bahasa yang jelas, persuasif, dan informatif dalam kemasan produk. Metode pelatihan yang digunakan meliputi praktik langsung dengan tujuan untuk memberikan pemahaman yang mendalam kepada siswa tentang pentingnya komunikasi yang efektif dalam mengemas produk projek kreatif yang diproduksi oleh siswa kuliner. Hal ini juga dapat meningkatkan kemampuan siswa dalam merancang kemasan yang menarik dan komunikatif. Hasil pelatihan menunjukkan peningkatan yang signifikan dalam keterampilan menggunakan Bahasa komunikatif pada kemasan produk. Kata kunci: Bahasa Komunikatif; Kemasan Produk; Siswa Kuliner